Stage 4S Neuroblastoma: What Are the Outcomes? A Systematic Review of Published Studies - Raitio, Arimatias; Rice, Michael J.; Mullassery, Dhanya; Losty, Paul D. (European Journal of Pediatric Surgery, 2020)
Introduction The prognosis of stage 4S/MS neuroblastoma has traditionally been reported as excellent, yet conflicting treatment protocols exist for this enigmatic disease. To critically address this question, we have undertaken a systematic review of published studies to accurately determine outcomes for infants with stage 4S/MS neuroblastoma.Materials and Methods Studies were identified using MEDLINE, Embase, and Cochrane databases using the relevant search terms. Literature reviews, case reports, and adult studies were excluded. Data were extracted independently following article selection by three authors and reviewed by the senior author.Results The original search retrieved 2,325 articles. Following application of exclusion criteria and removing duplicate data, 37 studies (1,105 patients) were included for final review. Overall patient survival was 84%. Twelve studies (544 patients) recorded MYCN status. Mortality in MYCN amplified tumors was 56%. Chromosome 1p/11q status was reported in four studies and 1p/11q deletion carried a 40% fatality rate. Management included observation only (201 patients, 8.5% mortality), surgical resection of primary tumor only (153 patients, 6.5% mortality), chemotherapy only (186 patients, 21% mortality), radiotherapy (5 deaths, 33% mortality), chemotherapy with surgery (160 patients, 10% mortality), surgery with radiotherapy (21 patients, 19% mortality), radiotherapy with chemotherapy (42 patients, 29% mortality), and surgery with chemotherapy and radiotherapy (27 patients, 33% mortality).Conclusion There is a significant mortality observed in stage 4S/MS neuroblastoma infants with a dismal outcome observed in those patients with MYCN amplification and 1p/11q deletion. Those patients suitably amenable for conservative management or surgery to excise the primary tumor carry the best prognosis.
Keywords: neuroblastoma; INRG stage MS; outcome; stage 4S